Experience with open schools and preschools in periods of high community transmission of COVID-19 in Norway during the academic year of 2020/2021 - Sara Stebbings; Torill Alise Rotevatn; Vilde Bergstad Larsen; Pål Surén; Petter Elstrøm; Margrethe Greve-Isdahl; Tone Bjordal Johansen; Elisabeth Astrup (BMC, 2022)
Abstract Background Schools and preschools have largely remained open in Norway throughout the pandemic, with flexible mitigation measures in place. This contrasts with many other high-income countries that closed schools for long periods of time. Here we describe cases and outbreaks of COVID-19 in schools and preschools during the academic year 2020/2021, to evaluate the strategy of keeping these open with infection prevention control measures in place. Methods In this descriptive study, the Norwegian Institute of Public Health initiated systematic surveillance for COVID-19 cases and outbreaks in schools and preschools in October 2020. Data was compiled from the national outbreak alert system VESUV, municipality websites, and media scanning combined with the national emergency preparedness register Beredt C-19. An outbreak was defined as ≥ 2 cases among pupils or staff within 14 days at the same educational setting. Settings were categorized as preschool (1-5-years), primary school (6-12-years), lower secondary school (13-15-years) and upper secondary school (16-18- years). We reported the incidence rate among preschool and school-aged pupils and gave a descriptive overview of outbreaks and included cases per educational setting. Results During the whole academic year, a total of 1203 outbreaks in preschools and school settings were identified, out of a total of 8311 preschools and schools nationwide. The incidence of COVID-19 in preschool- and school-aged children and the rates of outbreaks in these settings largely followed the community trend. Most of the outbreaks occurred in primary schools (40%) and preschools (25%). Outbreaks across all settings were mostly small (median 3 cases, range 2 to 72), however, 40 outbreaks (3% of total) included 20 or more cases. The larger outbreaks were predominantly seen in primary schools (43%). Conclusions We observed few large outbreaks in open schools and preschools in Norway during the academic year of 2020/2021, also when the Alpha variant was predominant. This illustrates that it is possible to keep schools and preschools open even during periods of high community transmission of COVID-19. Adherence to targeted IPC measures adaptable to the local situation has been essential to keep educational settings open, and thus reduce the total burden on children and adolescents.